EFFECTIVENESS OF USING INSTRUCTIONAL MATERIALS IN GUIDING YOUNG SCHOOL CHILDREN IN MATHEMATICS INSTRUCTION (UNIZIK Journal of STM Education, 2024)
This study examined the effectiveness of using instructional materials in guiding school children in mathematics instruction. The study was guided by four (4) research questions. A descriptive survey design was adopted to carry out the study. The population of the study was five hundred and eightysix (586) teachers. Simple random sampling technique was used to draw a sample of one hundred (100) primary school teachers from the population. The questionnaire developed for the study contained twenty (20) items which was used as an instrument for data collection. The validation of the instrument was done by three lecturers, one from Early Childhood and Primary Education and two from Education Foundation. The reliability of the instrument was determined using Person Product Moment Correlation Coefficient which gives a reliability index of 0.75. The analysis of the data collected was done using statistical mean. The result of the analyzed data revealed that the utilization of instructional materials in teaching Mathematics to children help to catch their attention span. Furthermore, among others, it was revealed that the usage of these materials tend to enhance the performance of school children in Mathematics as it makes the abstract concepts in mathematics easier to understand. Recommendation were made that teachers should incorporate or involve instructional materials in their Mathematics lessons to enable them achieve their lesson objectives as well as to help their pupils learn the intended lesson objectives. Furthermore, educational administrators should train and retain teachers on the use of instructional materials in teaching and to lay down guidelines for mathematic instruction.